Pengaruh Kompensasi Non Finansial Terhadap Prestasi Kerja Karyawan Pada Bank Syariah Mandiri Kota Sibolga - Safran Matondang; Heriyawan Hutagalung; Safriadi Pohan; Khairil Safli Pohan; Amaludin Sikumbang (EBISMA : Jurnal Ekonomi, Bisnis, Manajemen dan Akuntansi, 2025)
This study aims to determine the influence of non-financial compensation on employee performance at Bank Syariah Mandiri, Sibolga City. The research employed a quantitative approach with correlational data analysis techniques. The results showed a very strong and positive relationship between non-financial compensation and employee performance, with a correlation coefficient of 0.896. Validity tests confirmed that all questionnaire items were valid, and reliability tests indicated very high consistency for both variables. The analysis revealed that non-financial compensation contributes 80.24% to employee performance, while the remaining percentage is influenced by other factors not examined in this study. Hypothesis testing further supports that non-financial compensation significantly affects job performance. Therefore, enhancing non-financial aspects such as training, work recognition, and a supportive work environment is highly recommended to improve employee performance.